Does The Influence of Internship Experience on Career Intentions as a Professional Accountant? ? - Amalia, Diah; Mayasari, Mega; Ogundajo, Grace Oyeyemi (UNIVERSITAS NEGERI SURABAYA, 2021)
AbstractThis study describes the contribution of the internship experience as an antecedent to the relationship between the Theory of Planned Behavior (TPB) and career intentions as an accountant. This study applied a descriptive-quantitative method. In addition, data were analyzed using the Structural Equation Model-Partial Least Square (SEM-PLS). The results indicated that: (1) Sensory experiences had a positive but insignificant effect on attitude toward behavior. Besides, it had a negative and insignificant effect on subjective norms and perceived behavior control; (2) Affective experiences had a positive and significant effect on attitude toward behavior. Besides, it had a positive but insignificant effect on subjective norms and perceived behavior control; (3) Physical experiences had a negative and significant effect on attitude toward behavior. Besides, it had a positive but insignificant effect on subjective norms. Furthermore, it had a negative and significant effect on perceived behavior control; (4) Cognitive-creative experiences had a positive and significant effect on attitude toward behavior, subjective norms, and perceived behavior control; (5) Relation experiences had a positive and significant effect on attitude toward behavior, subjective norms, and perceived behavior control; (6) Attitude toward behavior, subjective norms, and perceived behavior control had a positive and significant effect on career intention as an accountant.